استخدام الذكاء الاصطناعي في قياس كفاية وملاءمة ادلة الاثبات الالكترونية في عمليات التدقيق (الشبكات العصبة التلافيفية نموذج). - ورقلي وليد; بوخالفي مسعود (جامعة الوادي University Of Eloued, 2024)
Digitizationis vital in the present time, especially with the huge spread of artificial intelligence applications. In this context, it has becomevery critical for everyone to adopt these technologies so as to keep up with the temporary circum stances. This research paperaims to analyze the use of artificial intelligence in measuring adequacy and appropriateness Evidence as well as its impact on audit practice, whether in terms of providingaccurate information or in terms of the possibility of relying on it in making rational decisions through the construction of an artificial intelligence model that utilize TEXT CNN algorithm to measure the sufficiency and appropriateness of the evidence. The paper concluded that artificial intelligence is effective in improving the quality of audit practice, leading to more precise valuations of the adequacy and relevance of financial statements. Keywords: electronic evidence;artificial intelligence; Convolutional Neural Networks; Audit.
The use of artificial intelligence in measuring the adequacy and appropriateness of electronic evidence in auditing processes (convolutional neural networks as a model).
Keywords: أدلة الاثبات الالكترونية; الذكاء الاصطناعي; الشبكات العصبية التلافيفية; التدقيق; electronic evidence; artificial intelligence; Convolutional Neural Networks; Audit